HUBUNGAN RELIGIUSITAS DAN SELF EFFICACY TERHADAP MOTIVASI BERPRESTASI PADA MAHASISWA WARGA BINAAN LEMBAGA PEMASYARAKATAN CIPINANG JAKARTA - Aliah B. P. Hasan, Istiqomah (Jurnal Psikologi, 2011)
In Indonesia, the first step and only effort to administer university degree program inside a prison was held in Cipinang CorrectionalInstitution Jakartain cooperation with Bung KarnoUniversity, a private university not far from the prison. This study discussed the relationship between religiosity,self effficacy andachievement motivation of student-prisonerresidents in this higher education program.This survey used quantitativeanalysisapproach, with 70 respondentsusingLikert questionnairesastools of measurement.Statistical analysisofthisstudywas usingsimplelinearregression formulawithSPSS-18 software.This study found positive relation between religiosity and selfefficacy to student achievement motivationinthe student-prisoner-residents withR square= 0.784. It means that this varibles influence wereas much as 78.4%. To completed their education,it need to improve religiosity and self efficacy as motivator way to success.